Art for policy and policy for art - Johnstone, Jean; O’Hare, Michael (Journal of public affairs education : J-PAE., 2024)
The intersection of arts and public policy is three-dimensional. A multitude of direct subsidy, regulatory, and support programs are advocated and managed as "arts policy," but a wide variety of non-arts-targeted realms such as tax law, public education, public health, and urban development and housing programs importantly influence artists and their encounters with their audiences. These interactions, and the complexity and thorniness born of the difficulty of clearly categorizing the arts as either market or non-market goods, as well as our difficulty in their valuation, make a particularly good area for teaching about public policy generally. And finally, policy of all kinds is too important to be made without the insights and guidance of artists, whose job is to show us the society we live in and who we are. Our "Arts and Cultural Policy" course explores this landscape for students in both fields.